Chemical modification and printability of shear-thinning hydrogel inks for direct-write 3D printing. (12th September 2018) - Smith, Patrick T.; Basu, Amrita; Saha, Abhijit; Nelson, Alshakim
Abstract: Shear-thinning hydrogels are often employed in direct-write 3D printing, however, the viscoelastic behaviors that define a printable hydrogel have not been fully established. Herein, we demonstrate a library of hydrogel inks based on the incorporation of water-soluble reactive meth(acrylate) monomers into F127-dimethacrylate hydrogels. This strategy afforded printed hydrogels with a broad range of chemical functionalities and mechanical properties. A systematic investigation was also performed to correlate the printability and mechanical properties to the viscoelastic properties of the hydrogel ink formulations. The materials with a high dynamic yield stress afforded extruded filaments that correlated well with the inner diameter of the printing nozzle. The static yield stress of the material was correlated to the extrusion pressure and print speed required for optimal printing. Thus, this study provides a guide for the future development of hydrogel inks for direct-write 3D printing along with a new set of functional hydrogel inks. Graphical abstract: Highlights: Library of hydrogel ink compositions for direct-write 3D printing. Printability was correlated to the viscoelastic properties of the hydrogel inks. Static and dynamic yield stress are important parameters for printability.